Evaluation of the effects of tramadol on analgesic response and locomotor activity on two different strains of laboratory mice - SYMEON, IRENE; POLISSIDIS, ALEXIA; BALAFAS, EVANGELOS; STASINOPOULOU, MARIANNA; ALEXAKOS, PAVLOS; VOYIATZAKI, CHRYSA; KOSTOMITSOPOULOS, NIKOLAOS (Journal of the Hellenic Veterinary Medical Society, 2018)
Analgesia of laboratory animals consists an important component in experimental studies where painful stimuli or procedures may take place. When choosing analgesics, the severity of pain along with the response to medication is among the factors that determine the choice of agent. Tramadol is a known synthetic opioid analgesic used to treat main acute or chronic pain including perioperative pain. The purpose of this study was to evaluate the analgesic response as well as the effect on locomotor activity in two different strains of mice after the intraperitoneal (i.p.) administration of tramadol. Subjects were 11-13 week-old male C57BL/6J (n=39) and BALB/cJ (n=38) mice, randomly assigned to receive either saline, tramadol 10 mg/kg or tramadol 40 mg/kg. Analgesia was measured using the hot-plate test, 30 or 60 minutes after drug administration while the open field test was used in order to assess locomotor activity. Both strains exhibited a significant increase of hot-plate latencies after administration of tramadol 40 mg/kg while the same dose induced significantly greater analgesia in BALB/cJ as compared with the C57BL/6J mice. BALB/cJ mice presented a dose-dependent decrease in locomotor activity following tramadol administration whereas C57BL/6J mice receiving 40 mg/kg tramadol showed hyperactivity. In conclusion, the lower dose of tramadol (10 mg/kg) has insufficient antinociceptive effects on acute thermal pain for both strains. The highest dose of tramadol used in this study (40 mg/kg) was greater than the one required for BALB/cJ mice, as they were under sedation for at least 60 minutes after drug administration. The same dose of tramadol appeared to be effective on C57BL/6J tramamice as latency times on the hot plate were significantly increased. Despite this fact, it is not a suitable choice as an analgesic, especially postoperatively, as it causes hyperactivity to this strain. Special concern should be given to the fact that tramadol’s analgesic and behavioral effects depend not only on its dosage, but also on the strain in which it is administered.